Influence of volatile anaesthetics on haematology and clinical chemistry in ferrets - Marie-Luise Schröder; Aline Reitmeier (BMC Veterinary Research)
Abstract Background During our years of working with ferrets in our laboratory animal facility, we observed that in several healthy young female ferrets, signs of anaemia could be detected during the entry examination although none of the ferrets expressed any clinical symptoms at the time of blood withdrawal. We aimed to compare the influence of inhalation anaesthesia with isoflurane and sevoflurane to restrained, awake ferrets on several blood parameters. After arrival at our facility all ferrets received a hormone chip to subdue oestrus. Routine blood withdrawal was conducted followed by routine blood work including haematology, clinical chemistry and electrolytes. Since the size of the cannula for implementation of the hormone chip is relatively large and the insertion probably quite painful the procedure was always performed during a short inhalation anaesthesia with isoflurane or sevoflurane. In ferrets showing anaemia (haemetocrit below 0.37 l/L, haemoglobin below 11 g/dL), we performed a control blood work (venous blood) the following week. In order to rule out an effect of inhalation anaesthesia on the laboratory results, the blood withdrawal was performed in restraint and awake ferrets without anaesthesia. The study was performed as randomized controlled crossover design. Results Thirty ferrets were enrolled, and divided in three groups. Comparison of the three methods (isoflurane, sevoflurane or restraint and awake without anaesthesia) of blood withdrawal showed statistically significant (p < 0.05) differences in most haematological parameters (e.g. red blood cell count, haematocrit), clinical chemistry parameters (e.g. total protein, albumin, alkaline phosphatase) and electrolytes (e.g. sodium, chloride and potassium). Restraint ferrets without anaesthesia showed no signs of anaemia. In anaesthetized ferrets, reticulocytes were about four to six times lower compared to ferrets anaesthetized with isoflurane or sevoflurane. Conclusions The results of the study suggest that inhalation anesthesia has a significant effect on hematological and biochemical parameters in ferrets. In particular, the detection of anemia in an animal undergoing inhalation anesthesia needs to be contextualized in a clinical setting and in research context.